Cellar: Securing Data for Twister (مجلة العلوم الإنسانية والتطبيقية, 2016)
Twister is an iterative framework for Google’s MapReduce programming. Twister runs within a cloud computing environment using several Virtual Machines (VMs) to divide up complex problems into manageable sections that are then dispersed to the VMs for processing. The goal of this paper is to evaluate Trusted Platform Module (TPM) as a protection measure for Twister.